DETERMINASI PRUDENCE ACCOUNTING PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK DI BEI - Afrizal Nilwan; Ulfa Rahmadila (Universitas Bandar Lampung (UBL), 2025)
This study aims to analyze the effect of capital structure, financial distress, and litigation risk on prudence accounting in transportation and logistics companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The study uses a quantitative approach utilizing secondary data sourced from the companies' annual financial reports. The sample was determined through a purposive sampling technique, resulting in 25 companies with a total of 75 company-year observations. Capital structure is proxied by the debt-to-equity ratio, financial distress is measured using the Grover model (G-Score), litigation risk is represented by the debt ratio, and prudence accounting is measured using accrual-based conservatism. Data that have met the classical assumption test are then analyzed using multiple linear regression with the help of IBM SPSS. The results show that capital structure does not significantly affect prudence accounting. Conversely, financial distress has a negative and significant effect, indicating that the higher the financial stress experienced by a company, the lower the level of prudence in its accounting practices. Meanwhile, litigation risk has been shown to have a positive and significant effect on prudence accounting, indicating that the increased potential for lawsuits encourages companies to prepare more conservative financial statements. This finding suggests that external pressures, particularly litigation risk, play a more dominant role in driving accounting prudence than internal factors such as capital structure.